Vasorelaxant effects of Vitis vinifera L. leaf extract on isolated rat aorta - MK Gharib Naseri; M Navid Hamidi; A Heidari (Institue of Medicinal Plants, ACECR, 2004)
Many reports have shown the various effects of grape (Vitis vinifera L.) seed extract for example antioxidant, protecting RBC against UV, also hypotensive, hypolipidemic and vasodilatory effects. We have recently shown the relaxatory effect of grape leaf extract on rat ileum and uterus and frog isolated heart rate and contractility. The aim of present study was to investigate the relaxant effect of Vitis vinifera leaf hydroalcoholic extract (VLHE) on isolated rat thoracic aorta contractions induced by phenylephrine and KCl, and the role of aorta endothelium on this action. Rat aorta was removed and placed in an organ bath containing Krebs-Henseleit solution and aorta contractions were recorded isometrically. The results demonstrate that the VLHE at 0.125, 0.25, 0.5, 1 and 2 mg/ml reduces the endothelial intact aorta contracted by phenylephrine (1 μM) significantly and dose-dependently. Endothelial denuded aorta showed the same relaxation but in much less extent. The IC50 of these two groups were 0.454±0.08 and 1.73±0.23 mg/ml respectively. VLHE also reduced the aorta contractions induced by KCl (80mM). The relaxatory effect of VHLE on KCl -induced contractions were less than those evoked by phenylephrine. Soluble guanylate cyclase inhibitor (methylene blue, 10 μM) and nitric oxide synthase inhibitor (L-NAME, 100μM) reduced the VHLE-induced relaxation in the intact aorta significantly but, atropine (1μM) was unable to decrease this vasorelaxant effect. These results suggest that the most vasorelaxant effect of VHLE on rat aorta is endothelium-dependent and also nitric oxide (NO) and cGMP are involved in this action.